DAMPAK TRADISI BEGAWE MERARIK TERHADAP SOSIAL EKONOMI MASYARAKAT ISLAM SASAK DI KOTA MATARAM - Saprudin, Saprudin (Universitas Islam Negeri Raden Fatah Palembang, 2019)
Tradition and culture are unique, sometimes like iron steel which absorbs the attractiveness and charm of the world of foreign tourism, but also sometimes has a moral problem. But judging by the preservation of the purity of cultural values, the pride of traditional traditions is important to preserve. Likewise, the begawe tradition draws on what is happening in the Sasak Muslim community on Lombok Island, which must be saved from the influence of global modernization that oppresses the purity values ​​of local culture. The lack of attention and concern of the government towards the begawe merarik tradition also determines the continuation of the traditional customs and culture of the Sasak community in the future.